Jauh Dibalik Pandangan, Menilik Sistem Pengendalian Manajemen Perusahaan PT. Unilever Indonesia - Charisma Bayu Ramadhan; Hwihanus Hwihanus (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Management Control System at PT. Unilever Indonesia still has weaknesses and deficiencies that need to be corrected. The implementation of strategic planning at Unilever Indonesia has not reached the desired level of optimality. Lack of top-level management involvement or deep understanding of market dynamics in the context of strategic planning. The aim of this research is to identify, analyze and understand the implementation of Management Control System tasks at PT. Unilever Indonesia, with a special focus on its weaknesses and shortcomings. This research uses qualitative research methods, which involve the use of observation techniques. Results The main findings involve a lack of top-level management involvement in strategic planning, leading to sub-optimality in setting corporate goals and priorities.